2011
DOI: 10.4103/0019-5413.83949
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous pinning for non-comminuted extraarticular fractures of distal radius

Abstract: Background:Various treatment modalities have been described for the treatment of extra-articular distal radius fractures each with its own merits and demerits. Most of the work done with percutaneous pinning has shown a significant residual stiffness of the hand and wrist. Our technique involves percutaneous pinning of the fracture and immobilization in neutral position of the wrist for three weeks. This study's aim was to examine the functional outcome of percutaneous K-wiring of these extra-articular distal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…Abhishek K Das et.al. in his study of percutaneous pinning and cast immobilization of the fracture found (81.25%) had excellent to good functional outcome. The study also concluded that, percutaneous pinning of distal radius fractures combined with early physiotherapy with wrist mobilisation provided good functional outcome and no loss of fracture alignment [9] . In our study 90% of the patients in k wire group showed excellent to good functional outcome 10% of patients showed satisfactory outcome.…”
Section: Discussionmentioning
confidence: 80%
“…Abhishek K Das et.al. in his study of percutaneous pinning and cast immobilization of the fracture found (81.25%) had excellent to good functional outcome. The study also concluded that, percutaneous pinning of distal radius fractures combined with early physiotherapy with wrist mobilisation provided good functional outcome and no loss of fracture alignment [9] . In our study 90% of the patients in k wire group showed excellent to good functional outcome 10% of patients showed satisfactory outcome.…”
Section: Discussionmentioning
confidence: 80%
“…reduction and cast immobilization. 10 Several studies reported the results of traditional manipulation and casting in contrast with other treatment modalities. Only casting isolated was not enough to maintain reduction, and may lead to poor functional and cosmetic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous pinning could provide more stability in addition to sufficient support, compared with closed reduction and cast immobilisation alone. 14 There are several studies reporting the outcomes of conventional manipulation and casting in comparison with other treatment options. Casting alone may not be enough to maintain anatomical position and reduction, leading to poorer functional and cosmetic results.…”
Section: Discussionmentioning
confidence: 99%